The Significance of Toll-Like Receptors in the Neuroimmunologic Background of Alcohol Dependence - Czerwińska-Błaszczyk, Agnieszka; Pawlak, Edyta; Pawłowski, Tomasz (Frontiers in Psychiatry, 2022)
Toll-like receptors (TLR) are a group of protein belonging to the family of Pattern Recognition Receptors (PRR) which have the ability to distinguish between an organism’s own antigens and foreign ones and to induce immunological response. TLR play a significant part in non-specific immunity but at the same time they are also a vital element linking non-specific response to the specific one. A growing number of data seems to indicate that the non-specific immunity mechanisms affect the development and sustenance of alcohol addiction. Alcohol damages the organism’s cells not only directly but also through an increase inintestinal permeability which induces innate immune response of peripheral blood cells. The signaling pathway of Toll-like receptors located on the surface of brain immune cells intensifies the inflammatory reaction and, through modifying gene expression of proinflammatory factors, unnaturally supports it. This overly protracted ‘sterile inflammatory reaction’ positively correlates with alcohol craving affecting also the functioning of the reward system structures and increasing the risk of relapse of alcoholism. Recurrent alcoholic binges sensitize the microglia and cause an escalation in inflammatory reaction which also leads to neurodegeneration. The induction of innate immunity signalling pathways exposes clinical symptoms of alcohol addiction such as increased impulsivity, loss of behavioural control, depressive-anxiety symptoms and cognitive dysfunctions. Traditional methods of treating alcohol addiction have tended to focus predominantly on reducing symptoms which – given the frequency of relapses – seems insufficient. The aim of the present paper is to discuss the role of toll-like receptors as elements of the immunity system which, together with the nervous system, plays a crucial part in the pathogenesis of alcohol addiction. We also wish to present pharmacotherapeutic perspectives targeted at the neuroimmunological mechanisms of alcohol addiction.